A coach's dozen: An update on building healthy, strong, and resilient young athletes - Faigenbaum, A. D.; Meadors, L. (Strength and Conditioning Journal, 2017)
The "coach's dozen" is a collection of 12 principles that will help youth coaches, physical education teachers, and pediatric exercise specialists maintain inclusive, sustainable, and enjoyable participation in exercise and sport.